The second book of Kings - Robinson, J. (Joseph), 1927- (Cambridge ; New York : Cambridge University Press, 1976)
The narrative now passes to the decline of the kingdoms of Israel and Judah and their territorial absorption into the empires of Assyria and Babylon. The compilers of 2 Kings attributed this downfall to the Hebrews' disregard of the prophets and of the covenant with God
List of maps and time chart -- The footnotes to the N.E.B. text -- What the book is about -- The earlier history of the Israelites -- Samaria and Israel -- The story told in I Kings -- Ahab and Elijah -- The influence of the prophets on the compiler of Kings -- The deuteronomists -- The point of view of the deuteronomists -- The end of the two kingdoms -- The motive for the writing of the book -- The Deuteronomic History -- How the book was compiled -- The story of King Hezekiah -- The chronology of Kings -- The faith of the writers -- Appendix -- Measures of length and extent -- Measures of capacity -- weights and coins -- Index
Includes bibliographical references (page 250) and index
Keywords: Bible. -- Commentaries